Open-Fit Domes and Children with Bilateral High-Frequency Sensorineural Hearing Loss: Benefits and Outcomes - Johnstone, Patti M.; Yeager, Kelly R.; Pomeroy, Marnie L.; Hawk, Nicole (Journal of the American Academy of Audiology, 2018)
Open-fit domes (OFDs) coupled with behind-the-ear (BTE) hearing aids were designed for adult listeners with moderate-to-severe bilateral high-frequency hearing loss (BHFL) with little to no concurrent loss in the lower frequencies. Adult research shows that BHFL degrades sound localization accuracy (SLA) and that BTE hearing aids with conventional earmolds (CEs) make matters worse. In contrast, research has shown that OFDs enhance spatial hearing percepts in adults with BHFL. Although the benefits of OFDs have been studied in adults with BHFL, no published studies to date have investigated the use of OFDs in children with the same hearing loss configuration. This study seeks to use SLA measurements to assess efficacy of bilateral OFDs in children with BHFL.To measure SLA in children with BHFL to determine the extent to which hearing loss, age, duration of CE use, and OFDs affect localization accuracy.A within-participant experimental design using repeated measures was used to determine the effect of OFDs on localization accuracy in children with BHFL. A between-participant experimental design was used to compare localization accuracy between children with BHFL and age-matched controls with normal hearing (NH).Eighteen children with BHFL who used CE and 18 age-matched NH controls. Children in both groups were divided into two age groups: older children (10–16 yr) and younger children (6–9 yr).All testing was done in a sound-treated booth with a horizontal array of 15 loudspeakers (radius of 1 m). The stimulus was a spondee word, “baseball”: the level averaged 60 dB SPL and randomly roved (±8 dB). Each child was asked to identify the location of a sound source. Localization error was calculated across the loudspeaker array for each listening condition.A significant interaction was found between immediate benefit from OFD and duration of CE usage. Longer CE usage was associated with degraded localization accuracy using OFDs. Regardless of chronological age, children who had used CEs for <6 yr showed immediate localization benefit using OFDs, whereas children who had used CEs for >6 yr showed immediate localization interference using OFDs. Development, however, may play a role in SLA in children with BHFL. When unaided, older children had significantly better localization acuity than younger children with BHFL. When compared to age-matched controls, children with BHFL of all ages showed greater localization error. Nearly all (94% [17/18]) children with BHFL spontaneously reported immediate own-voice improvement when using OFDs.OFDs can provide sound localization benefit to younger children with BHFL. However, immediate benefit from OFDs is reduced by prolonged use of CEs. Although developmental factors may play a role in improving localization abilities over time, children with BHFL will rarely equal that of peers without early use of minimally disruptive hearing aid technology. Also, the occlusion effect likely impacts children far more than currently thought.
Keywords: children; hearing loss; outcomes